A collaborative ICT-based proposal to implement the AOA mini project in a ninth-grade class at Naranjo Bilingual High School in 2021 - Mora Jara, Noelia 1996-; Pérez Quirós, Joselyn 1996-; Varela Méndez, Carlos 1997-; Vargas Jiménez, David 1997-; Vargas Vásquez, José Miguel 1986- ([San Ramón, Alajuela, Costa Rica], 2022)
At the beginning of 2020 and up to 2021, the world underwent the acute phase of the health crisis of the Covid-19 pandemic, including widespread restrictions on mobility and gatherings. As a result, educational institutions in Costa Rica had to work entirely online, forcing teachers around the country to depend on information and communication technologies (ICTs) for their lessons. Within that context, this research examines the fulfillment of collaborative learning principles in an AOA mini project supported by ICTs and their perceived impact on the students' performance in a 9th-grade class at Naranjo Bilingual High School. The study followed a Classroom Action Research method grounded in a qualitative approach. The MEP AOA mini-project was carried out in a reading and writing class. In small groups, students created a blog on Edublogs, consisting of four written entries about environmental issues. The results showed that implementing ICT-based collaborative projects with the AOA mini-project structure allowed students to develop 21st century skills such as problem-solving, digital literacy, creativity, and collaboration. This research serves as a reference for English teachers in Costa Rica to enrich and improve the development of the AOA mini project. As a limitation, the students reported a need for further training on the ICT platforms used for the study since several supplementary ICT tools were involved. Furthermore, the population involved in the study was small, which does not allow for generalizable results.
Proyecto de graduación (licenciatura en enseñanza del inglés)--Universidad de Costa Rica. Sede de Occidente, 2022
Keywords: INGLES -- ENSEÑANZA SECUNDARIA -- TECNOLOGIA DE LA INFORMACION; INGLES -- ENSEÑANZA CON AYUDA DE COMPUTADORAS; RENDIMIENTO ACADEMICO